Financial Inclusion for Women in Mexico: a Tool for their Empowerement - Herrera García, Adolfo Federico (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The article analyzes the financial inclusion of women and their relationship with empowerment in the current Mexican society as official figures show that 39% of adult women have a bank account and only 25% have a credit card, which It frames a great dependence of women with men in financial matters. Currently, there is no established theory on the financial inclusion of women, although the importance of promoting it as a tool to achieve the empowerment of excluded groups has been highlighted. It shows the positive impact of decreasing female financial exclusion in our country, to then determine through the analysis of major components the variables that have greater explanatory power in this phenomenon; In addition, a hierarchical cluster analysis is used to establish the level of each state of the Republic in terms of access and use of financial services in traditional and microfinance institutions.Given this, it can be said that there is an important gender gap and that measures must be implemented to increase the participation of women in the financial sector in order to improve their socioeconomic conditions and their quality of life, which allows them to grow in different environments of everyday life.
Keywords: financial inclusion; empowerment; gender equity; access; microfinance